2016
DOI: 10.1152/ajpheart.00372.2015
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-phosphate signaling contributes to cardiac inflammation, dysfunction, and remodeling following myocardial infarction

Abstract: Sphingosine 1-phosphate (S1P) mediates multiple pathophysiological effects in the cardiovascular system. However, the role of S1P signaling in pathological cardiac remodeling following myocardial infarction (MI) remains controversial. In this study, we found that cardiac S1P greatly increased post-MI, accompanied with a significant upregulation of cardiac sphingosine kinase-1 (SphK1) and S1P receptor 1 (S1PR1) expression. In MI-operated mice, inhibition of S1P production by using PF543 (the SphK1 inhibitor) am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 36 publications
5
93
1
Order By: Relevance
“…tive hypertrophy to maladaptive hypertrophy with clear evidence of cardiac fibrosis and dysfunction. 52,53 It has recently been shown that inhibition of SphK1/S1P signaling ameliorates infarction-induced cardiac remodeling and dysfunction, 54 and our finding of improvement in cardiac function after SphK1 inhibition without decreases in RVSP and RV hypertrophy might be attributable to a direct therapeutic benefit in maladaptive RV hypertrophy. Another factor is the short therapeutic window (3 weeks).…”
Section: Discussionsupporting
confidence: 54%
“…tive hypertrophy to maladaptive hypertrophy with clear evidence of cardiac fibrosis and dysfunction. 52,53 It has recently been shown that inhibition of SphK1/S1P signaling ameliorates infarction-induced cardiac remodeling and dysfunction, 54 and our finding of improvement in cardiac function after SphK1 inhibition without decreases in RVSP and RV hypertrophy might be attributable to a direct therapeutic benefit in maladaptive RV hypertrophy. Another factor is the short therapeutic window (3 weeks).…”
Section: Discussionsupporting
confidence: 54%
“…This is associated with increased SphK1 and S1P 1 expression, suggesting that MI can regulate transcriptional activity of the genes encoding these proteins [52]. In this study administration of PF-543…”
Section: Sphk1 Inhibitors and Cardiac Hypertrophymentioning
confidence: 51%
“…FTY720 is converted to FTY720 phosphate, which is a S1P 1 functional antagonist (see [11] for review) and FTY720 is also a SphK1 inhibitor [8]. These authors also showed that SphK1/S1P/S1P 1 -dependent STAT3 signaling and inflammation was modulated by FTY720, thereby reducing post-MI cardiac remodeling and dysfunction [52]. Therefore, SphK1 might participate in the chronic pro-inflammatory and fibrotic responses during the hypertrophic process that eventually leads to cardiomyocyte apoptosis and RV failure.…”
Section: Sphk1 Inhibitors and Cardiac Hypertrophymentioning
confidence: 98%
See 1 more Smart Citation
“…31 S1P binds to S1P receptor 1 and is thought to exert a cardioprotective effect through multiple pathways, including Akt signaling. 29 Although there is some controversy as to whether S1P/S1P receptor 1 signaling is cardioprotective, 32 the balance of evidence suggests that activation of S1P signaling may be a potential therapeutic target for HF.…”
Section: Cardiac Metabolismmentioning
confidence: 99%